Strengthening the character of cooperation through ethnomathematical understanding in the traditional game Rangku Alu - Martanti, Fitria; Nurkaenah, Nurkaenah; Sholikhin, Sholikhin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Reading is one of the fundamental skills that students must master from the early stages of education. Good reading ability not only supports students’ understanding of various subjects but also contributes to the development of critical thinking skills. However, low reading interest and limited reading comprehension abilities remain significant challenges in primary education. This condition affects the quality of learning and limits students’ ability to understand information in depth. Therefore, the use of engaging and effective learning media is necessary to improve students’ reading abilities. This study aims to examine the effect of using flashcard media on the reading comprehension ability of fourth-grade elementary school students. The research employed a quantitative approach with a quasi-experimental design. The research population consisted of all fourth-grade students, with a total sample of 36 students, divided into 17 students in the experimental group and 19 students in the control group. Data were collected through a pretest and a posttest, and then analyzed using tests of normality, homogeneity, and hypothesis testing. The results of the study indicate that the use of flashcard media has a significant positive effect on students’ reading comprehension ability. These findings suggest that interactive visual media can serve as an effective pedagogical strategy to improve the quality of reading instruction and strengthen literacy skills among elementary school students.